Digital Succession: Addressing the Disposition of Juan's Online Digital Assets upon his Death - Manicad III, Macario B.; Perez, Alyanna D. (Diliman, Quezon City, Philippines: University of the Philippines College of Law)
Online digital assets, which are intangible assets, form part of a person's inheritance. The existing laws on succession allow the transmission of one's digital assets to another upon his death either by will or operation of law. Filipinos must be aware of this so they can better plan the disposition of these assets upon their death, if they wish to, and their heirs can account for these accordingly. However, that the idea of digital assets is an emerging concept and there is no jurisprudence yet on the matter, the authors address several legal issues on the succession of digital assets. These issues include defining digital assets, determining the question of ownership and transferability of said assets, and consequently confronting the issue on the rights of administrators, executors, or heirs to access the decedent's accounts and materials uploaded online in light of the privacy agreements the latter enters into with internet companies. Notwithstanding said issues, the Civil Code is sufficient to govern the transmission of digital assets.
Keywords: Online digital assets - Liability (Law)